Nursery Cities: Urban Diversity, Process Innovation, and the Life Cycle of Products - Duranton, Gilles; Puga, Diego (American Economic Review, 2001)
This paper develops microfoundations for the role that diversified cities play in fostering innovation. A simple model of process innovation is proposed, where firms learn about their ideal production process by making prototypes. We build around this a dynamic general-equilibrium model, and derive conditions under which diversified and specialized cities coexist. New products are developed in diversified cities, trying processes borrowed from different activities. On finding their ideal process, firms switch to mass production and relocate to specialized cities where production costs are lower. We find strong evidence of this pattern in establishment relocations across French employment areas 1993–1996. (JEL R30, O31, D83)